Examining the influence of demographic variables on mathematics test anxiety - Bista, Rajendra; Poudel, Prasanna; Baral, Dipesh (American Journal of STEM Education, 2024)
Mathematics test anxiety adversely impacts students’ performance, engagement, and attitudes toward STEM fields. In this study, we examined how age, gender, and education influence math test anxiety. Results from 102 participants indicate younger students experience higher anxiety than older students, and females report more anxiety than males, especially shortly before a test. Contrary to expectations, educational attainment did not significantly relate to anxiety during surprise quizzes. Findings underscore the complexity of math anxiety, shaped by demographic variables and influenced by parental attitudes, pedagogical approaches, and intergenerational factors. Addressing math anxiety requires targeted strategies that consider individual differences and environmental influences. Interventions to reduce math anxiety can improve learning outcomes, support STEM persistence, and foster positive experiences in mathematics.